2018
DOI: 10.3390/su10113954
|View full text |Cite
|
Sign up to set email alerts
|

Distant Interactions, Power, and Environmental Justice in Protected Area Governance: A Telecoupling Perspective

Abstract: Equity has become a major concern in efforts to conserve nature. However, in the Global South, inequitable social impacts of conservation usually prevail. We investigate barriers to equitable governance of four protected areas through an innovative approach linking the tri-dimensional framing of environmental justice with the notion of telecoupling. We conceptualize the creation, support, and implementation of protected areas as telecoupling processes that involve flows, actors, and action situations, and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 109 publications
1
42
0
Order By: Relevance
“…Most of the research on telecoupling to date has been conducted in terrestrial environments. Some studies have been done involving terrestrial protected areas, which have shown the extent to which even remote terrestrial reserves are connected and impacted in diverse ways by distant systems [84][85][86][87]. Effects of telecoupling on terrestrial protected areas are varied, including positive effects seen in the case of outside federal aid rescuing a protected area recovering from a natural disaster [84] and negative effects such as in the case of the rights of indigenous groups in protected areas made more vulnerable via extractive demands from transnational trade flows [85].…”
Section: Opportunities For Applying the Telecoupling Framework To Marmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research on telecoupling to date has been conducted in terrestrial environments. Some studies have been done involving terrestrial protected areas, which have shown the extent to which even remote terrestrial reserves are connected and impacted in diverse ways by distant systems [84][85][86][87]. Effects of telecoupling on terrestrial protected areas are varied, including positive effects seen in the case of outside federal aid rescuing a protected area recovering from a natural disaster [84] and negative effects such as in the case of the rights of indigenous groups in protected areas made more vulnerable via extractive demands from transnational trade flows [85].…”
Section: Opportunities For Applying the Telecoupling Framework To Marmentioning
confidence: 99%
“…Some studies have been done involving terrestrial protected areas, which have shown the extent to which even remote terrestrial reserves are connected and impacted in diverse ways by distant systems [84][85][86][87]. Effects of telecoupling on terrestrial protected areas are varied, including positive effects seen in the case of outside federal aid rescuing a protected area recovering from a natural disaster [84] and negative effects such as in the case of the rights of indigenous groups in protected areas made more vulnerable via extractive demands from transnational trade flows [85]. Some valuable telecoupling work has been done in marine environments on understanding distal causes and effects of seabird migration [71], the Peruvian fishery industry [88], and mapping 'extra-local' ecosystem services in the marine context [24].…”
Section: Opportunities For Applying the Telecoupling Framework To Marmentioning
confidence: 99%
“…However, the telecoupling framework does not make explicit the wider implications of distant interactions to society and to the environment in terms of power, control and unequal outcomes. For this reason, several researchers on telecoupling have proposed a more heuristic telecoupling approach that includes institutions, actor networks and governance processes to make power relationships in decision-making across distances more explicit (Friis et al 2015;Eakin et al 2017, Oberlack et al 2018. In this contribution, we propose to connect the concept of telecoupling with a geopolitical approach, which pays attention to unfolding power relationships within conservation spaces and how these relations are forged through distant interactions.…”
Section: Sébastien Boillat and Frédéric Girautmentioning
confidence: 99%
“…In order to safeguard forest ecosystems, a key landscape planning tool is the establishment of protected areas (PAs) (Thomas and Gillingham, 2015;Melillo et al, 2016). Some scholars consider PAs as "telecoupled territories" in themselves, chiefly because of the large role played by international actors in their establishment and management, and the dependence of PAs on external financial flows (Boillat et al, 2018). The area of land under legal protection regimes has been increasing for decades (Watson et al, 2014) and calls to vastly expand it are emerging (Dinerstein et al, 2019).…”
Section: Introduction: Agricultural Intensification and Human Well-bementioning
confidence: 99%